A Comparison of Three-Dimensional and Two-Dimensional Cephalometric Evaluations of Children with Cleft Lip and Palate - Tulunoglu, Ozlem; Esenlik, Elcin; Gulsen, Ayse; Tulunoglu, Ibrahim (European Journal of Dentistry, 2011)
Objectives: The aim of this retrospective study was to compare the consistency of orthodontic measurement performed on cephalometric films and 3D CT images of cleft lip and palate (CLP) patients. Methods: The study was conducted with 2D radiographs and 3D CT images of 9 boys and 6 girls aged 7-12 with CLP. 3D reconstructions were performed using MIMICS software. Results: Frontal analysis found statistical differences for all parameters except occlusal plane tilt (OcP-tilt) and McNamara analysis found statistical differences in 2D and 3D measurements for all parameters except ANS-Me and Co-Gn; Steiner analysis found statistical differences for all parameters except SND, SNB and Max1-SN. Intra-group variability in measurements was also very low for all parameters for both 2D and 3D images. Conclusions: Study results indicate significant differences between measurements taken from 2D and 3D images in patients with cleft lip and palate. (Eur J Dent 2011;5:451-458)
Keywords: 3D reconstruction; Computerized tomography; Cephalometry; CLP